Click, Clack, Moo : I Love You! - Cronin, Doreen; Lewin, Betsy (New York : Atheneum Books For Young Readers, 2017)
Little Duck is working hard making valentines for everyone and decorating for the Valentine's Day dance, but what happens when an unexpected guest arrives?
Keywords: Valentine's Day -- Juvenile fiction; Farm life -- Juvenile fiction; Ducks -- Juvenile fiction; Animals -- Juvenile fiction; Dance parties -- Juvenile fiction; Valentine's Day -- Fiction; Farm life -- Fiction; Ducks -- Fiction; Animals -- Fiction; Dance parties -- Fiction; Picture books